Cost-effectiveness of chemotherapy for advanced and recurrent cervical cancer: a systematic review - Inami, Katsuaki (Frontiers in Health Services, 2025)
IntroductionAdvanced and recurrent cervical cancer often requires palliative chemotherapy and is associated with poor prognosis. Recently, various systemic therapies—including cytotoxic drugs, anti-angiogenic agents, and immune checkpoint inhibitors—have been evaluated for their cost-effectiveness.MethodsWe conducted a systematic review of English language-based research publications reporting incremental cost-effectiveness ratios (ICERs) for chemotherapy-based treatments in advanced or recurrent cervical cancer. Literature was retrieved from PubMed, Scopus, and Web of Science without date restrictions and screened based on predefined eligibility criteria. A total of 10 studies were included.ResultsTraditional first-line platinum-based doublet chemotherapy (e.g., cisplatin plus paclitaxel) was consistently found to be cost-effective, with ICERs well below common willingness-to-pay (WTP) thresholds. The addition of bevacizumab improved survival but increased costs, yielding borderline or unfavorable ICERs (e.g., 155,000/QALY in the U.S.). Immunotherapy agents such as pembrolizumab and cadonilimab offered clinical benefits but often exceeded WTP thresholds, particularly in low- and middle-income settings. Cemiplimab had an ICER of 111,000/QALY as a second-line treatment, near the upper U.S. WTP threshold, while agents like tisotumab vedotin were not economically viable at current prices. Cost-effectiveness varied across regions depending on pricing, healthcare systems, and local WTP thresholds.DiscussionAlthough newer agents provide incremental survival benefits, their high costs often outweigh QALY gains. Policymakers and clinicians should consider the economic impact of adopting such therapies and prioritize value-based strategies, including price negotiations, biosimilar use, and biomarker-guided patient selection. Future research should promote evidence-based pricing and access models to support sustainable cancer care worldwide.